Neuro-ophthalmology illustrated - Biousse, Valérie (Thieme, 2020)
"Neuro-ophthalmology is an "overlap" specialty, encompassing all disorders that affect the parts of the central nervous system related to vision. Neuro-Ophthalmology Illustrated, Third Edition by world-renowned neuro-ophthalmologists and professors Valérie Biousse and Nancy J. Newman expands on the widely acclaimed prior editions, lauded with awards by the Association of American Publishers and the British Medical Association. The updated text reflects diagnostic advances such as optical coherence tomography and features new high-quality images and videos. The text starts with neuro-ophthalmic and funduscopic examinations, visual fields, commonly used ancillary testing methods, and an overview of visual loss. Subsequent chapters detail a wide array of conditions including retinal vascular diseases, optic neuropathies, disc edema, disorders of higher cortical function, abnormal visual perceptions, diplopia, orbital syndromes, cavernous sinus and orbital vascular disorders, nystagmus/other ocular oscillations, and disorders of the eyelid. Final chapters are dedicated to nonorganic neuro-ophthalmic symptoms and signs, diagnosis of headache and facial pain, neurologic and systemic disorders that commonly have neuro-ophthalmologic manifestations, and an approach to management of the visually impaired patient. Key Highlights Concise text coupled with more than 600high-quality images enhances understanding of complex concepts Easily accessible within pertinent sections, 69 video clips cover a wide spectrum of topics such as examination techniques, normal eye movements, eye movement disorders, and pupil findings Clinical pearls, flow charts, boxes, tables, and a highly detailed index at the end of the text improve retention and assimilation of knowledge This book is essential reading for students, ophthalmology, neurology, and neurosurgery residents, as well as seasoned clinicians in these specialties. At once authoritative and easy to read, this resource provides readers with all the tools they need to diagnose and manage neuro-ophthalmologic disorders"--